Teachers’ and Students’ Perceptions of Artificial Intelligence (AI) Technology in Learning Activities - Sholikhah, Siti Sintiawati; Zamzami, Nagata; Sulistyaningsih (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to explore the perceptions of teachers and students regarding the use of Artificial Intelligence (AI) technology in classroom learning activities. Specifically, it investigates how AI is perceived in terms of its effectiveness and potential integration into the educational environment. Employing a descriptive qualitative approach with a case study design, the research was conducted at SMK Bhakti Norma Husada, Nganjuk, East Java, during May to June 2025. Data were collected through Likert-scale questionnaires and semi-structured interviews, involving purposively selected teachers and randomly selected Grade X–XI students. The findings indicate that most teachers hold a positive perception toward the use of AI in education, recognizing its potential to enhance personalized learning, improve evaluation processes, and support interactive teaching methods. However, a few expressed concerns related to limited training and the possible reduction of the teacher’s role. In contrast, students’ responses were predominantly neutral, suggesting a lack of direct experience and limited understanding of AI technology. Nevertheless, a notable portion showed openness and a willingness to explore its use in learning. In conclusion, while teachers exhibit readiness to embrace AI in their instructional practices, students remain cautiously receptive. To support effective AI integration, it is essential to provide targeted training, improve digital literacy, and create opportunities for both teachers and students to engage with AI in meaningful ways. The study highlights the importance of institutional support and strategic planning in harnessing AI as a valuable educational tool.